Interlimb coordination during step-to-step transition and gait performance - Andreia S. P. Sousa (2015)
Most energy spent in walking is due to step-to-step transitions. During this phase, the interlimb coordination assumes a crucial role to meet the demands of postural and movement control. The authors review studies that have been carried out regarding the interlimb coordination during gait, as well as the basic biomechanical and neurophysiological principles of interlimb coordination. The knowledge gathered from these studies is useful for understanding step-to-step transition during gait from a motor control perspective and for interpreting walking impairments and inefficiency related to pathologies, such as stroke. This review shows that unimpaired walking is characterized by a consistent and reciprocal interlimb influence that is supported by biomechanical models, and spinal and supraspinal mechanisms. This interlimb coordination is perturbed in subjects with stroke.